Older-to-Older Living Kidney Transplantation: A New Paradigm - Cátia Raquel Figueiredo; Círia Sousa; Sofia Ventura; Gonçalo Cruz; Manuela Almeida; José Silvano; Jorge Malheiro; Sofia Pedroso; La Salete Martins (Publicações Ciência e Vida, 2022)
Older to older living kidney transplantation is an acceptable alternative to avoid dialysis, improve quality of life and maintain favorable long-term outcomes of patients with end-stage kidney disease. However, the management of these patients is complex and the acceptance of older donors and recipients to kidney transplantation remains controversial. The older recipients usually have several comorbidities that may complicate the postoperative course and increase the risk of end-stage kidney disease. We present a clinical case of living kidney transplantation between an older donor and recipient, both over 70 years old, who evolved to a stage 3 chronic kidney disease, without proteinuria, hypertension, or other complications, three years after transplantation. Our case reinforces favorable outcomes in older living transplantation, both for recipient and donor, as has been demonstrated in several published studies.